(untitled) (Asian Journal of Pharmaceutics (AJP), 2023)
Introduction: Artesunate (ART) is a prodrug used as an antimalarial agent that acts by malarial protein damage through alkylation. Pyrimethamine (PYR) is an antiprotozoal agent that acts by interfering with the synthesis of tetrahydrofolic acid. Sulfadoxine is a dihydropteroate synthetase inhibiter which makes difficulty in parasite reproduction. A stability-indicating high-performance liquid chromatography (HPLC) technique has been established for the quantification of PYR, sulfadoxin, and ART applying design of experiment. Material and Methods: The phosphate buffer (pH 3.0):acetonitrile (80: 20) was used as the mobile phase, and hypersil BDS C18 (250 × 4.6 mm; 4 m) column at a flow rate of 1 mL/min was used for the chromatographic separation. The detection wavelength was set at 237 nm. The mobile phase was optimized using 32 full factorial design. Results and Discussion: The optimized method contains the retention times of PYR, sulfadoxin, and ART at 3.653, 4.920, and 8.310 min, respectively. The method shows a good linearity in the concentration range of 0.5–2.5 μg/mL for PYR, 10–50 µg/mL for sulfadoxin, and 4–20 µg/mL for ART. The stability study of the drugs was performed by acid, alkali, oxidation, thermal, and photolytic degradation. Conclusion: The proposed stability indicating HPLC method was found to be simple, specific, practical, accurate, quick, and affordable. It was also suitable for the routine analysis, quality control, and percentage degradation of pharmaceutical preparations containing these drugs either individually or in combination.